FLIP(L): the pseudo‐caspase. (12th March 2020) - Smyth, Peter; Sessler, Tamas; Scott, Christopher J.; Longley, Daniel B.
Abstract : Possessing structural homology with their active enzyme counterparts but lacking catalytic activity, pseudoenzymes have been identified for all major enzyme groups. Caspases are a family of cysteine‐dependent aspartate‐directed proteases that play essential roles in regulating cell death and inflammation. Here, we discuss the only human pseudo‐caspase, FLIP(L), a paralog of the apoptosis‐initiating caspases, caspase‐8 and caspase‐10. FLIP(L) has been shown to play a key role in regulating the processing and activity of caspase‐8, thereby modulating apoptotic signaling mediated by death receptors (such as TRAIL‐R1/R2), TNF receptor‐1 (TNFR1), and Toll‐like receptors. In this review, these canonical roles of FLIP(L) are discussed. Additionally, a range of nonclassical pseudoenzyme roles are described, in which FLIP(L) functions independently of caspase‐8. These nonclassical pseudoenzyme functions enable FLIP(L) to play key roles in the regulation of a wide range of biological processes beyond its canonical roles as a modulator of cell death. Abstract : FLIP(L) is to date the only true pseudo‐caspase identified in the human proteome. As a classical pseudoenzyme, it functions as a regulator of its active homologs, the apoptosis‐initiating caspases, caspase‐8 and caspase‐10. Additionally, FLIP(L) functions independently of these caspases. These nonclassical pseudoenzyme functions enable FLIP(L) to play key roles in the regulation of a wide range of biological processes beyond its canonical roles as a modulator of cell death.